Statistical Analysis of the Removal of Acid Fuchsin Dye Using Zeolite 5A - Nada Sadoon Ahmedzeki; Atheer Kamil (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
Investigation of the adsorption of acid fuchsin dye (AFD) on Zeolite 5A is carried out using batch scale experiments according to statistical design. Adsorption isotherms, kinetics and thermodynamics were demonstrated.  Results showed that the maximum removal efficiency was using zeolite at a temperature of 93.68751 mg/g. Experimental data was found to fit the Langmuir isotherm and pseudo second order kinetics with maximum  removal of about 95%.  Thermodynamic analysis showed an endothermic adsorption. Optimization was made for the most affecting operating variables and a model equation for the predicted efficiency was suggested.